(untitled) (Sirte University Journal of Humanities, 2025)
This research aims to uncover the elements of textual cohesion and their impact on linking the text’s parts and achieving cohesion and cohesion between them. This is done through an application to an Arabic linguistic text, namely the words of Lady Aisha (may God be pleased with her) in supplication for mercy for her father, Abu Bakr (may God be pleased with him), in two of her sermons (peace be upon her). I followed the steps of the descriptive method, with its procedures including description, analysis, interpretation, and deduction, in an attempt to uncover the dimensions of the elements of textual cohesion contained in Arabic linguistic texts from the perspective of modern rhetorical studies. The study also analyzes the aesthetics of phrasing, composition, and structure in illuminating meaning from a critical perspective. The research consists of an introduction and a preface, two chapters, a conclusion, and a glossary of references and sources. The research yielded results, the most important of which are: the necessity of monitoring linguistic development by applying modern linguistic achievements to the Arabic language to demonstrate the convergence between various languages.